Click Beetles, Alaus spp. (Insecta: Coleoptera: Elateridae) - Robert E. Woodruff (EDIS)
Because of their striking appearance and their large size, beetles of the genus Alaus are commonly brought to the attention of nursery inspectors and Cooperative Extension Service agents. Three species in this genus, A. myops (Fabricius), A. oculatus (Linnaeus), and A. patricius (Candeze) are found in Florida. This document is EENY-085 (originally published as DPI Entomology Circular No. 109), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999.